2003
DOI: 10.1037/0021-9010.88.3.476
|View full text |Cite
|
Sign up to set email alerts
|

Predicting cross-cultural training performance: The validity of personality, cognitive ability, and dimensions measured by an assessment center and a behavior description interview.

Abstract: This study examined the validity of a broad set of predictors for selecting European managers for a cross-cultural training program in Japan. The selection procedure assessed cognitive ability, personality, and dimensions measured by assessment center exercises and a behavior description interview. Results show that the factor Openness was significantly related to cross-cultural training performance, whereas cognitive ability was significantly correlated with language acquisition. The dimensions of adaptabilit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
98
0
4

Year Published

2007
2007
2018
2018

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 212 publications
(109 citation statements)
references
References 81 publications
(142 reference statements)
7
98
0
4
Order By: Relevance
“…The same concept has also been referred to as adaptability (Lievens, Harris, Van Keer, & Bisqueret, 2003;Redmond & Bunyi, 1993) and has been identified by expatriates as an important contributor to successful completion of international assignments (Arthur & Bennett, 1995;Arthur, Bennett, Edens, & Bell, 2003;Graf, 2004). Research has linked flexibility to various intercultural outcomes.…”
Section: Flexibilitymentioning
confidence: 99%
See 1 more Smart Citation
“…The same concept has also been referred to as adaptability (Lievens, Harris, Van Keer, & Bisqueret, 2003;Redmond & Bunyi, 1993) and has been identified by expatriates as an important contributor to successful completion of international assignments (Arthur & Bennett, 1995;Arthur, Bennett, Edens, & Bell, 2003;Graf, 2004). Research has linked flexibility to various intercultural outcomes.…”
Section: Flexibilitymentioning
confidence: 99%
“…Openness also predicted lower desire to terminate the assignment. Another study showed that openness to experience was positively related to cross-cultural training performance (Lievens, Harris, Van Keer, & Bisqueret, 2003).…”
Section: Big Five Traitsmentioning
confidence: 99%
“…For example Lievens et al (2003) mention that some previous scholars showed that cross-cultural training contributes to expatriate adjustment and performance. However, other scholars found the results to be inconclusive (Littrell et al 2006).…”
Section: Cross-cultural Trainingmentioning
confidence: 99%
“…Empirical research attests to this. Recently, Lievens, Harris, Van Keer, and Bisqueret (2003) examined whether two assessment center exercises were valid predictors of European executives who were selected to work in Japan. They found that one of the exercises, the group discussion exercise, was a very powerful predictor of future performance as rated by Japanese supervisors later on.…”
Section: Importance Of Matching the Predictor To The Criterionmentioning
confidence: 99%